1984
DOI: 10.1104/pp.76.2.372
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Anabolism in Germinating Glycine max (L.) Seeds

Abstract: ABSTRACIActive polyamine biosynthesis occurs in the embryonic axis, but not in the cotyledons, during germination of Glyciac max (L.) further elucidated. To understand the potential roles of polyamines in cellular metabolism, it is necesary to clarify whether changes in the content of polyamines in general or a specific polyamine is causally linked to, or merely a consequence of, plant growth and development. In this study, polyamine levels and complexities were determined in the cotyledon, hypocotyl hook, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…As far as cotyledons are concerned, DAO activity is detectable only at stage 1 in soybean, while in bean it is high and increases throughout germination. In the latter case this might be due to hydrolysis of storage substances and to the transport of polyamines and/or their metabolites to the embryo axis, as shown to occur in the same species (Bagni 1970), In soybean cotyledons 40^50% of the lysine resulting from the breakdown of the cotyiedonary proteins ends up in cadaverine whose synthesis has been observed in hypocotyls and radicles (Lin 1984) as well as its oxidation (Tab. 1), In conclusion, the different patterns of DAO activity observed are probably linked to the regulation of the cellular level of polyamines.…”
Section: Disctissionmentioning
confidence: 94%
“…As far as cotyledons are concerned, DAO activity is detectable only at stage 1 in soybean, while in bean it is high and increases throughout germination. In the latter case this might be due to hydrolysis of storage substances and to the transport of polyamines and/or their metabolites to the embryo axis, as shown to occur in the same species (Bagni 1970), In soybean cotyledons 40^50% of the lysine resulting from the breakdown of the cotyiedonary proteins ends up in cadaverine whose synthesis has been observed in hypocotyls and radicles (Lin 1984) as well as its oxidation (Tab. 1), In conclusion, the different patterns of DAO activity observed are probably linked to the regulation of the cellular level of polyamines.…”
Section: Disctissionmentioning
confidence: 94%
“…The biological phenomena of adaptation to stress are complex and many biological macromolecules, including proteins and lipids, must be involved in the processes of such adaptation. Molecular chaperones are assumed to be involved in adaptation to stress because of their ability to refold partially denatured polypeptides, to bind to denatured polypeptides so as to prevent or slow down their aggregation and to dissolve hydrophobic aggregates of proteins formed under normal or stress conditions [7, 14-171. It has been shown that some plant seedlings can acquire induced thermotolerance to lethal high temperatures through a prior treatment at a lower, non-lethal high temperature [18]. Since treatment at non-lethal high temperatures that induces thermotolerance also induces the synthesis of heat-shock proteins, it is assumed that these proteins participate in protection of cells from the effects of extreme high temperatures [18].…”
mentioning
confidence: 99%
“…In plants the polyamine cadaverine (1,5-diaminopentane) is synthesized from lysine by lysine decarboxylase enzyme (LDC,EC 4.1.1.18). This compound is present in various bacteria and several higher plant families such as Gramineae, Poaceae, Solanaceae and in particular in Leguminosae (Bagni et al 1986;Lin 1984;Rodrı ´guez et al 2000;Smith and Wilshire 1975). In the Leguminosae family, decarboxylation is the main pathway of cadaverine synthesis, although it can also be synthesized from homoarginine via homoagmatine, metabolites that are present during seed germination (Smith 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some Leguminosae contain a large amount of cadaverine (Federico and Angelini 1988) which can be converted into aminopropylcadaverine and bis (aminopropyl)cadaverine, as also suggested in H. tuberosus explants by Bagni et al (1981). Although the plant distribution of cadaverine and the activity and localization of diamine oxidases cadaverine catabolic enzymes (Lin 1984;Smith and Barker 1988;Scoccianti et al 1990;Torrigiani and Scoccianti 1995), were extensively studied in Leguminosae during seed germination and development, little attention has been given to lysine decarboxylase activity and its regulation in vitro and in vivo. The present study examines lysine decarboxylase activity in both soluble and particulate fractions of soybean (Glycine max (L.) Meer cv.…”
Section: Introductionmentioning
confidence: 99%